2019
DOI: 10.1016/j.jiac.2019.01.015
|View full text |Cite
|
Sign up to set email alerts
|

The effects of antifungal stewardship programs at a tertiary-care teaching hospital in Japan

Abstract: Patients with invasive fungal diseases (IFDs) generally have a high mortality rate, and resistance to antifungal drugs and the high costs associated with it have led to recent problems, necessitating the appropriate use of antifungals. To this end, we launched Antifungal Stewardship Programs (AFSPs) in our hospital. Patients who were systemically administered antifungals from January 2011 to December 2016 were enrolled this study and divided into pre-intervention and intervention groups. No significant differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 16 publications
(21 reference statements)
0
26
1
Order By: Relevance
“…Recommendations for ancillary management measures in candidaemia are included in the Australian, 40 US 41 and European 42 guidelines and include requirement for early CVC removal, ophthalmological consultation, echocardiography, repeat blood cultures and a 14 day duration of therapy following clearance of blood cultures. Strategies to improve adherence to candidaemia guideline recommendations, including timely initiation of appropriate antifungals and implementation of a bundle of care, have been shown to improve patient outcomes 18,[43][44][45][46] including a demonstrated mortality benefit. 43,44 Pettit et al 25 implemented the most extensive bundle of care incorporating all recommended management strategies in addition to the requirement for infectious diseases consultation.…”
Section: Discussionmentioning
confidence: 99%
“…Recommendations for ancillary management measures in candidaemia are included in the Australian, 40 US 41 and European 42 guidelines and include requirement for early CVC removal, ophthalmological consultation, echocardiography, repeat blood cultures and a 14 day duration of therapy following clearance of blood cultures. Strategies to improve adherence to candidaemia guideline recommendations, including timely initiation of appropriate antifungals and implementation of a bundle of care, have been shown to improve patient outcomes 18,[43][44][45][46] including a demonstrated mortality benefit. 43,44 Pettit et al 25 implemented the most extensive bundle of care incorporating all recommended management strategies in addition to the requirement for infectious diseases consultation.…”
Section: Discussionmentioning
confidence: 99%
“…Improve diagnostic efforts Low Märtson et al [ 40 ] Retrospective Candida species Therapeutic drug monitoring of posaconazole 1–3 years Patients with haematological malignancies. The University Medical Center Groningen, the Netherlands No 64% was the adequate posaconazole exposure; in the longitudinal analysis from all the confounders, only dose had a significant effect on posaconazole concentrations Low Kawaguchi et al [ 41 ] Single-centre, observational Candida species Antifungal stewardship programs (AFSPs) 1–3 years Patients who received systemic antifungals at the Osaka City University Hospital (980-bed, tertiary-care teaching hospital) Yes As the appropriate selection of antifungals increases, a decrease in antifungal usage and cost reduction also occurs. This trend leads to improved prognoses of patients with candidemia Low Ito-Takeichi et al [ 42 ] Single-institutional prospective cohort Candida species 1‐3, β - d -glucan (βDG) testing 1–2 days In patients receiving intravenous antifungals at the 614-bed Gifu University Hospital No Parental antifungal use was significantly reduced Low Cavalieri et al [ 46 ] Retrospective Candida species MALDI-TOF mass spectrometry / Vitek 2 1–2 days Hospitalized patients Yes An average 18 h faster microbial ID and antimicrobial susceptibility test results Low Steuber et al [ 18 ] Single-centre, retrospective, observational Candida species T2 Candida Panel (T2CP) …”
Section: Methodsmentioning
confidence: 99%
“…In a systematic review, Bienvenu et al concluded that active intervention, such as post-prescription review, had more impact than guideline implementation. 255 Reported outcomes include reduced mortality, [256][257][258] reductions in time to appropriate antifungal therapy, [259][260][261] reduced antifungal consumption, [256][257][258]262 reduced number of patients treated for IC, 256 improved guideline or bundle of care adherence, 260,263 increase in optimal antifungal prescribing 262,264,265 and reduced cost. 257,262 Implementation of an educational antimicrobial stewardship (AMS) programme focusing on appropriate antibacterial therapy resulted in a reduction in the incidence and mortality rate of hospital-acquired candidaemia.…”
Section: Afs and Guideline Implementationmentioning
confidence: 99%